Ecology and evolution of dung beetles - Simmons, Leigh W., 1960-; Ridsdill-Smith, J., 1942-; Wiley InterScience (Online service) (Chichester, West Sussex, UK ; Hoboken, N.J. : Wiley-Blackwell, 2011)
"This book describes the evolutionary and ecological consequences of reproductive competition for scarabaeine dung beetles. As well as giving us insight into the private lives of these fascinating creatures, this book shows how dung beetles can be used as model systems for improving our general understanding of broad evolutionary and ecological processes, and how they generate biological diversity. Over the last few decades we have begun to see further than ever before, with our research efforts yielding new information at all levels of analysis, from whole organism biology to genomics. This book brings together leading researchers who contribute chapters that integrate our current knowledge of phylogenetics and evolution, developmental biology, comparative morphology, physiology, behaviour, and population and community ecology. Dung beetle research is shedding light on the ultimate question of how best to document and conserve the world's biodiversity. The book will be of interest to established researchers, university teachers, research students, conservation biologists, and those wanting to know more about the dung beetle taxon"--
Reproductive competition and its impact on the evolution and ecology of dung beetles / Leigh W. Simmons and T. James Ridsdill-Smith -- The evolutionary history and diversification of dung beetles / T. Keith Philips -- Male contest competition and the evolution of weapons / Robert Knell -- Sexual selection after mating : the evolutionary consequences of sperm competition and cryptic female choice in onthophagines / Leigh W. Simmons -- Olfactory ecology / G.D. Tribe and B.V. Burger -- Explaining phenotypic diversity : the conditional strategy and threshold trait expression / Joseph Tomkins and Wade Hazel -- Evolution and development : Onthophagus beetles and the evolutionary development genetics of innovation, allometry, and plasticity / Armin Moczek -- The evolution of parental care in the onthophagine dung beetles / John Hunt and Clarissa House -- The visual ecology of dung beetles / Marcus Byrne and Marie Dacke -- The ecological implications of physiological diversity in dung beetles / Steven L. Chown and C. Jaco Klok -- Dung beetle populations : structure and consequences / Tomas Roslin and Heidi Viljanen -- Biological control : ecosystem functions provided by dung beetles / T. James Ridsdill-Smith and Penny B. Edwards -- Dung beetles as a candidate study taxon in applied biodiversity conservation research / Elizabeth S. Nichols and Toby A. Gardner.
Includes bibliographical references and indexes.
Print version record.
Keywords: Dung beetles -- Ecology; Dung beetles -- Evolution; Insect societies; Science; Zoology; SCIENCE -- Life Sciences -- Zoology -- General; Electronic books